Profile of the problem of the adolescent with parents as Indonesian migrant workers - Yandri, Hengki; Juliawati, Dosi (Konselor, 2018)
Adolescents who have parents as Indonesian Workers have a tendency to be closed, quiet, less able to socialize, have been learning problems and lack discipline that needs the attention of all parties. Therefore, this study aims to uncover adolescent problems, including personal problems, social relations, and academic problems. This study used a qualitative method of intrinsic case study approach with two teenagers as respondents. Data collection by in-depth interviews, and the validity of the data by data triangulation, then analyzed through data reduction, data presentation and conclusion drawing. The research findings revealed that the problems experienced by respondents were not self-confidence, lack of attention from parents, not confident, anxiety, economic problems, broken relationships with parents and siblings, difficulty socializing, not confident away from parents, easy feeling sad when talking about parents, careless, daydreaming and not listening to the advice of others. Then their social relations are good, and some are difficult to get along with the community and like to be alone. After that their parents support the lectures that theme have undergone, but there are also respondents who experience financial constraints and poor learning skills in college.